Implementing Circular Economy Elements in the Textile Industry: A Bibliometric Analysis - Hora, Simina Teodora; Bungau, Constantin; Negru, Paul Andrei; Radu, Andrei-Flavius (Sustainability, 2023)
Significant environmental and social issues confront the textile and apparel industries, including resource depletion and excessive textile waste. Implementing circular economy principles is essential for the sustainability of this industry. The present paper is a bibliometric analysis study type designed to identify collaborative networks, prolific countries, journals, and influential articles pertaining to the implementation of the circular economy in the textile and apparel industries that may serve as a starting point for an in-depth understanding of the subject, facilitating the knowledge of essential bibliometric parameters for pre-publication phases. The data were extracted from the Web of Science and analyzed using both the Web of Science web interface and the VOSviewer software version 1.6.19. The bibliometric data were divided into two distinct periods to analyze the evolution of this subject over time: from 1975 to 2010 and from 2011 to 2023. In the first period, the most productive country was the United States, with 527 publications, accounting for 10.81% of the scientific output during that time. In the second period, China emerged as the most productive country, with 2478 published documents, constituting 18.44% of the total production in this period. During the first period, Istanbul Technical University was the most active institution, with 91 publications (1.87% of the total production), while in the second period the Indian Institute of Technology System was the most productive, with 265 documents (1.95%). These key findings demonstrate the textile industry’s commitment to sustainable and environmentally friendly practices. They also highlight the industry’s adoption of advanced technologies and its exploration of new research areas; but there is still room for improvement, which is why continuous research implemented through future research areas is essential.